Interventions that challenge established and accepted clinical practice: lessons learnt from a process evaluation of the STOP-APE trial - Agnieszka Ignatowicz; Sheila Greenfield; Pooja Gaddu; Clare Prince; Mark Toshner; Graham Robinson; Jonathan Rodrigues; Susan Jowett; Simon Noble; Michael Newnham; Alice Turner; Daniel Lasserson (Health Technology Assessment)
Background Developing and implementing interventions that change clinical practice can be challenging and complex. Such interventions can be particularly difficult when attempting to change established behaviours and practices. While extensive literature on implementation of interventions that focus on changing clinical practice exists, understanding of the difficulties involved in implementing interventions that go against accepted clinical practice is limited. Objectives To describe the challenges involved in delivering a complex intervention that goes against established clinical practice, using a clinical trial assessing the balance of benefits and risks of withholding anticoagulation for subsegmental pulmonary embolism as an example. Design and methods This study draws from a process evaluation conducted as part of a clinical trial. The evaluation utilised semistructured interviews with patients and clinicians during the trial’s internal pilot phase to investigate the acceptability of withholding anticoagulant medication and participants’ experiences within the trial. The data were analysed using the framework method. Setting and participants Eight patients with subsegmental pulmonary embolism (six females and two males) and three acute care clinicians (two males and one female) from five trial sites were interviewed. Results Our findings indicated that factors such as clinician equipoise, discomfort with certain patient characteristics, and effective patient communication are closely connected and significantly impact both the process of changing clinical practice and the conduct of the trial. Clinicians faced difficulties in approaching eligible patients for trial participation, especially when a diagnosis and treatment plan had already been provided by another clinician. The tension between maintaining clinical equipoise and addressing the needs of unwell patients further complicated decisions, particularly when withholding anticoagulation in those with severe symptoms or multiple comorbidities. Communication about the risks and benefits of non-medication strategies for pulmonary embolism was also challenging, with concerns about undermining patient trust. Patients, on the other hand, expressed considerable anxiety about not receiving anticoagulants, with their perspectives on study participation and treatment heavily influenced by their prior health experiences and ongoing medical conditions. The active involvement of clinicians in the consent process had a positive effect on patients’ perceptions and experiences, with many feeling reassured in knowing they could contact clinical staff if needed. Limitations Small sample size of patients and clinicians across limited study sites; single method of data collection. Conclusions Our results highlight the multifaceted challenges when attempting to conduct studies that challenge accepted practices and norms. These complexities are deeply intertwined, influencing both clinical decision-making and patient recruitment for those studies. Future work Future research should focus on developing strategies to help clinicians maintain equipoise and communicate the risks and benefits of interventions, while also deepening the understanding of patients’ experiences and perceptions to enhance recruitment strategies. Ethical approval Wales REC 6, Reference: 20/WA/0256, approved 30 September 2020. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR128073. Plain language summary It can be difficult to carry out studies that change how we commonly treat a particular illness. It can be especially hard to implement studies when they try to change the way we work, which has been in place for many years. We tried to carry out a trial that considered the benefits and risks of not giving anticoagulation (medication that reduces the blood’s ability to clot) to people with a very small blood clot in the lung, called a subsegmental pulmonary embolism. We undertook interviews with patients and clinicians as part of the clinical trial to explore what participants thought about not receiving anticoagulant medication and how they felt about the study. We found that it was harder for clinicians to invite patients to take part in this trial when they had already been told about their blood clot and offered standard treatment of anticoagulant medication. The patients we talked to were worried about the diagnosis and the fact that they might become more unwell if they do not take anticoagulants. Some patients thought that taking part in the study meant withdrawing treatment altogether because they might all be put in the ‘no anticoagulants’ group of the study, rather than being allocated to either continuing treatment or stopping treatment (called randomisation). We concluded that these challenges were closely linked and had a big impact on changing clinical practice and recruiting patients for the trial. Future research should focus on finding best ways to help clinicians stay unbiased when deciding on treatments and clearly explain the risks and benefits to patients. It should also explore patients’ experiences and views to improve how we recruit people for such trials. The trial was prospectively registered as ISRCTN15645679.